Analisis Penatausahaan dan Penyusunan Laporan Pertanggungjawaban Bendahara dalam Peningkatan Kinerja pada Dinas Ketahanan Pangan dan Peternakan Kabupaten Madiun - Tri Mukti Wijayanti; Mohammad Sofyan; Hartirini Warnaningtyas (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This research aims to analyze the process of administration and preparation of the financial reports Treasurer’s Accountability Report (LPJ) on the performance at the Dinas Ketahanan Pangan dan Peternakan Kabupaten Madiun, and to evaluate its compliance with applicable regulations. The research method uses descriptive qualitative with data collection techniques through observation, interviews, and documentation. Informants consist of Budget Users (PA), Financial Management Officers-SKPD (PPK-SKPD), Technical Management Officers of Activities (PPTK), and Academics. The results indicate that the process of administration and preparation of the LPJ has been carried out well and orderly in accordance with Permendagri No. 77 of 2020 and Perbup Madiun No. 142 of 2023. There is an increase in the realization of the spending budget by 2% in 2025 compared to 2024. Realization in 2024 was 93.40% and in 2025 was 95.40% which shows the organization’s performance from a financial aspect. The main obstacles faced are technical factors in the form of internet network instability in the regional government information system (SistemInformasi Pemerintah Daerah-SIPD) and errors in inputting account codes at the planning stage which hamper the realization of expenditures so that they do not comply with the plan. Researchers suggest the need to improve network infrastructure, strengthen planning coordination through an internal control system, and develop human resource capacity periodically to optimize reporting accountability and performance at the Dinas Ketahanan Pangan dan Peternakan Kabupaten Madiun.